Nutritional evaluation of taekwondo athletes - Singh, K. (International Journal of Innovative Science and Research Technology, 2024)
This study aims to evaluate the dietary intake of elite Indian Taekwondo athletes to determine their nutritional adequacy and compare it with other combat sports. Five male athletes participated, with an average age of 24.5 ± 2.5 years, weight 64.5 ± 5.5 kg, height 170 ± 5.5 cm, BMI 22.5 ± 0.5 kg/m2, and body fat percentage 9.5 ± 4.0%. The analysis was based on a three-day dietary record. The findings revealed nutritional inadequacies in protein and fiber intake, despite generally adequate intake of most macro- and micronutrients. Further studies during different training and competition phases could provide more insight into the nutritional risks associated with weight-category sports and the strategies used for competitive advantage.